Dosimetric verification and quality assurance for intensity-modulated radiation therapy using Gafchromic® EBT3 film. Issue 1 (28th November 2017) - Iqbal, Khalid; Mazhar Iqbal, Muhammad; Akram, Muhammad; Altaf, Saima; Ahmad Buzdar, Saeed
Abstract: Purpose: This study aimed to examine the dosimetric properties of Gafchromic® EBT3 film and intensity-modulated radiation therapy quality assurance (IMRT QA). Materials and methods: Beams characteristics dosimetric properties and 20 IMRT plans were created and irradiated on Varian dual-energy DHX-S Linac for 6 and 15 MV energies. EBT3 films were analysed using 'film Pro QA 2014' software. Results: The dosimetric comparison of EBT3 film (for red channel dosimetry) and ionisation ion chamber measurement showed that average deviations of symmetry, flatness, central axis, penumbra (left) and penumbra (right) of dose profile were 0·18, 1·34, 0·49%, 3·68 and 3·61 mm for 6 MV and 0·10, 1·3, 0·45, 2·65 and 2·71 mm for 15 MV, respectively. The blue and green channels dosimetry showed greater dose deviation as compared with red channel. IMRT QA verification plan complied about 95% at all different criteria. Reproducibility, stability and face orientation of film were within 1·4% for red channel. Conclusions: The results advocate that the film can be used not only for dosimetric assessment but also as a reliable IMRT QA tool.